Knowledge Dynamics in AI-Driven Natural Science Research: A Bibliometric Review Using VOSviewer - Babawande Emmanuel Olawale (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2026)
This study examines how artificial intelligence is reshaping knowledge production within the natural sciences. It maps research growth, collaborative structures, and thematic developments to clarify how AI-driven methods are being adopted across global scientific communities. A bibliometric review was conducted using data from Scopus-indexed publications from 2020 to 2025. The quantitative bibliometric approach was employed to examine the structural, thematic, and collaborative aspects of AI-driven research within the natural sciences, combining performance analysis to evaluate publication output, citation impact, and productivity trends with science mapping using VOSviewer to visualise co-authorship networks, keyword co-occurrences, and co-citation relationships. For this review, the Boolean search query that was employed includes